Quality of life in the EU countries and regions before and during the COVID-19 pandemic years - Lakócai, Csaba (Bulletin of Geography. Socio-economic Series, 2025)
The latest pandemic had disparate impacts on the quality of life of individuals around the world. The primary hypothesis guiding this research is that the impacts on quality of life during the pandemic years are associated with the pre-pandemic social and environmental conditions. However, the effects varied across certain groups of countries and regions, as well as across different years. In order to substantiate this assumption, an analysis will be conducted on the 27 member states of the European Union at the national and NUTS2 regional levels. The regression analysis demonstrates that life expectancy in 2021 decreased more where it was lower before the pandemic. In 2020 and 2022, there were no significant differences in terms of life expectancy changes across the countries. However, we get a more nuanced picture at the regional level. In terms of life satisfaction, a convergence between the EU countries is observed by 2022.